2010
DOI: 10.3324/haematol.2010.031674
|View full text |Cite
|
Sign up to set email alerts
|

Repeated PR1 and WT1 peptide vaccination in Montanide-adjuvant fails to induce sustained high-avidity, epitope-specific CD8+ T cells in myeloid malignancies

Abstract: The online version of this article has a Supplementary Appendix. BackgroundWe previously showed that vaccination with one dose of PR1 and WT1 peptides induces transient anti-leukemia immunity. We hypothesized that maintenance of a sustained anti-leukemia response may require frequent boost injections. Design and MethodsEight patients with myeloid malignancies were enrolled in this phase II study, and 6 completed 6 injections of PR1 and WT1 peptides in Montanide-adjuvant with GM-CSF, every two weeks. ResultsBot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 54 publications
4
106
0
Order By: Relevance
“…The vaccine was generally well tolerated and the toxicity profile consistent with other WT1 vaccine-adjuvant combinations [21][22][23][24][25] ( Table 2). The montanide adjuvant is a known irritant, 26 and many of the most frequent toxicities consisted of mild to moderate local reactions and inflammation: injection site reaction (46%), fatigue (32%), skin induration (32%), and injection site pruritus (27%).…”
Section: Safety and Toxicitymentioning
confidence: 64%
“…The vaccine was generally well tolerated and the toxicity profile consistent with other WT1 vaccine-adjuvant combinations [21][22][23][24][25] ( Table 2). The montanide adjuvant is a known irritant, 26 and many of the most frequent toxicities consisted of mild to moderate local reactions and inflammation: injection site reaction (46%), fatigue (32%), skin induration (32%), and injection site pruritus (27%).…”
Section: Safety and Toxicitymentioning
confidence: 64%
“…This may in part reflect the low levels and limited tissue distribution of WT-1 expression in healthy subjects. [18][19][20] Recently, Rezvani et al also demonstrated declining T-cell responses to WT-1 in patients repeatedly vaccinated with WT-1 peptides, 64 suggesting that these responses are highly regulated. Lehe et al have also recently shown that sensitization of T cells with a WT-1 peptide presented by DRB 1 0402 in the presence of high concentrations of IL-2 preferentially stimulates the generation of CD25 ϩ FOX P3 ϩ GITR ϩ CD127 Ϫ regulatory T cells capable of inhibiting CD8 ϩ WT-1-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II clinical trial in AML and high-risk MDS using a WT1 peptide vaccine demonstrated that an immunologic response was observed in 44% patients, and objective clinical responses were observed in 10 out of 17 AML patients [18]. While there are reports from small case series which have suggested that WT1 vaccination can have long term efficacy in patients [19,20], other groups have observed that that repeated peptide vaccination in Montanide failed to induce sustained high-avidity, epitope-specific T cell responses in treated patients [21]. In addition, Lehe et al [22] generated WT1 specific T-cell clones which carried a CD4…”
Section: Wt1 Is a Leukemia Associated Antigenmentioning
confidence: 99%